Evaluation of Cu, Fe, and Pb for Fast Neutron Shielding using Monte Carlo PHITS Simulation - Sitti Yani (Newton-Maxwell Journal of Physics, 2024)
Developing effective neutron shielding materials for applications like muon tomography requires understanding the interaction of neutrons with different materials. This study investigates the effectiveness of heavy metals (Cu, Fe, and Pb) as neutron shields using Monte Carlo PHITS simulations with fast neutrons (0.1, 0.5, and 1 MeV). Simulation results show that the intensity of transmitted neutrons decreases with increasing material thickness and atomic number (Pb > Fe > Cu). How far a particle travels before stopping is determined by two factors: its initial neutron energy and how likely it is to interact with the material it's passing through. These findings provide valuable insights into designing optimal neutron shielding materials for various applications.